Aqad Salam Haal Dalam Perspektif Madzhab Syafi’i dan Penerapannya Dalam Aqad – Aqad Jual Beli Kontemporer - Miftah Farid; Muhammad Arifin Badri; Andre Nirwana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Disputes among scholars in the realm of ijtihadiyah issues are commonplace, including one of which is the realm of fiqh, especially buying and selling transaction, it is said